Understanding IPv6 - Mun, Youngsong. (Springer US : Imprint: Springer, 2005)
IPv6, Internet Protocol Version 6, is the next-generation internet protocol designed by the IETF to replace the current IPv4, now nearly 20 years old. As the new IPv6 protocol replaces IPv4, professionals need a practical and detailed reference and introduction that explains the new capabilities and changes. Especially since new and modified features and integration of additional protocols underpin IPv6, a well-organized overview becomes even vital. Here readers find a full explanation of what they need to know to function optimally in the new environment. Based on the latest IETF meetings, Understanding IPv6 provides not only the basics but details on transition and optimization mechanisms, modifications in DNS, mobile IPv6, and security issues. In addition, Understanding IPv6 explains each topic based on the latest IETF published documents and: Compares IPv6 and IPv4, e.g., crucial aspects such as protocol and addressing architecture, expanded address features, modifications of DNS, and header formats. Clarifies the many related protocols that need to be mastered in optimizing IPv6, plus core features such as neighbor discovery, address autoconfiguration, and DHCPv6. Details internetworking mechanisms and mobility services with many examples and figures. Devotes full coverage to transition mechanisms, especially Teredo. Understanding IPv6 is a reference work for graduate level students, communications engineers and researchers.